2019
DOI: 10.1016/j.fertnstert.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial compaction (decreased thickness) in response to progesterone results in optimal pregnancy outcome in frozen-thawed embryo transfers

Abstract: Objective: To evaluate whether the change in endometrial thickness between the end of the estrogen phase and the day of embryo transfer has an impact on the pregnancy rate in frozen-thawed embryo transfer (FET) cycles. Design: Retrospective observational cohort study. Setting: Single tertiary care medical center. Patient(s): Ultrasound images in 274 FET cycles were reviewed. All patients underwent endometrial preparation with the use of hormonal therapy. Interventions(s): Ultrasound measurements of endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 20 publications
(19 reference statements)
7
70
4
2
Order By: Relevance
“…ETC was an independent risk factor for CPR and OPR. This conclusion is consistent with that of Jigal Haas's study [3].…”
Section: Discussionsupporting
confidence: 93%
“…ETC was an independent risk factor for CPR and OPR. This conclusion is consistent with that of Jigal Haas's study [3].…”
Section: Discussionsupporting
confidence: 93%
“…Data from this study showed that endometrial thickness in recipients prior to and following progesterone had no impact on pregnancy outcomes. More recently, another cohort study including 271 FET cycles also evaluated endometrial thickness on both the end of the estrogen phase and the day of embryo transfer [14]. Interestingly, they found that a decreased endometrium (endometrial compaction) in response to progesterone results in better pregnancy outcome in FET cycles, which means that the greater the degree of compaction, the higher the ongoing pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another point is that the endometrial situation of each patients is re-evaluated on the morning of embryo transfer day also by trans-vaginal ultrasonic examination, which is a more accurate way to measure endometrial thickness. In Haas’s study, endometrial thickness was measured by means by pelvic (transabdominal) ultrasound [14]. This may explain the controversy between the totally opposite results from these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we noted that some recent studies [20,21] that have looked at the effect of endometrial changes between the transfer day and the starting of progesterone day, on clinical pregnancy outcomes. Our results suggest that endometrial compaction on transplantation day has a negative effect on clinical pregnancy outcomes.…”
Section: Plos Onementioning
confidence: 96%